SOSIALISASI STRATEGI INOVATIF PENGELOLAAN SAMPAH BERBASIS PEMBERDAYAAN MASYARAKAT DI DESA DAWAN, KABUPATEN KLUNGKUNG, BALI - Budi Shantika; Ni Kadek Winda Yanti; Milida Lessu; I Made Dedik Setiawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Waste management is a significant environmental challenge in Indonesia, particularly in rural areas such as Dawan Village, Klungkung Regency, Bali. With the increasing volume of household waste, consisting of both organic and inorganic materials, innovative strategies are required to address this issue. This community service and outreach program aimed to implement a community-based waste management system through an educational and collaborative approach. The methods used included socialization, training, and the application of the 3R principles (Reduce, Reuse, Recycle). This program not only succeeded in raising environmental awareness but also provided economic benefits through waste processing into compost and other products. The study recommends improving waste management facilities, establishing continuous educational programs, and fostering closer collaboration between the community, government, and private sector to create a cleaner and more sustainable environment in Dawan Village